High Maternal Total Cholesterol Is Associated With No-Catch-up Growth in Full-Term SGA Infants: The Japan Environment and Children’s Study - Kaneko, Kayo; Ito, Yuki; Ebara, Takeshi; Kato, Sayaka; Matsuki, Taro; Tamada, Hazuki; Sato, Hirotaka; Saitoh, Shinji; Sugiura-Ogasawara, Mayumi; Yatsuya, Hiroshi; Kamijima, Michihiro; , The Japan Environment Children’s Study Group; et al. (Frontiers in Endocrinology, 2022)
Objectives: Infants born small-for-gestational-age (SGA) with no catch-up growth (No-CU) are at high risk of intellectual and developmental disabilities. However, factors leading to No-CU among SGA infants are unclear. This study aimed to examine the association between maternal total cholesterol (TC) in mid-pregnancy and No-CU at 3 years among full-term SGA infants. Study Design: The Japan Environment and Children’s Study (JECS) is a nationwide prospective birth cohort study. We extracted a total of 2,222 mothers and full-term SGA infants (length and/or weight <-2 standard deviation [SD]) without congenital abnormalities from the original JECS cohort comprising a total of 104,062 fetal records. According to the distribution of maternal TC in the entire cohort, participants were classified into nine groups per each 5th percentile with the 20th–79th percentile (204–260 mg/dL) as the reference group. No-CU was defined by a Z-score of height at 3 years <– 2 SD according to the growth standard charts for Japanese children. Multivariable adjusted logistic regression models were carried out using multiple imputation. Additionally, multiple adjusted restricted cubic spline model was performed in the complete dataset. Results: A total of 362 (16.3%) children were No-CU at 3 years. After adjusting for Z-score of birth weight, age of mother, smoking status, weight gain during pregnancy, breastfeeding and meals frequency at 2 years, and parent’s heights, the odds ratio (95% confidence intervals) of No-CU was 2.95 (1.28-6.80) for children whose maternal TC were in the highest category (≥294 mg/dL), compared to the reference group. Multiple adjusted restricted cubic spline model had shown non-linear trend of the significant association between high maternal TC and No-CU (p for linear trend = 0.05, p for quadratic trend <0.05). Conclusion: High maternal TC at mid-pregnancy was associated with No-CU among SGA infants. Such infants should be carefully followed up to introduce appropriate growth hormonal treatment. The findings may support previous animal experimental studies which indicated that maternal high fat diet exposure induces impairment of growth and skeletal muscle development in the offspring. Future studies are required to elucidate the detailed mechanism.